Acmella calva (DC.) R.K. Jansen Flower: A Comprehensive In vivo Study of its Central and Peripheral Analgesic, Hypoglycemic, Antidepressant, and Anti-Diarrheal Properties (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Acmella calva (DC.) R.K. Jansen (Local name “Surzo konna”) is a Southeast Asian perennial herb mostly used in rural areas as an ailment of dental disorders. This study involved the evaluation of peripheral and central analgesic activities, hypoglycemic, anti-diarrheal and anti-depressant activities of the methanolic extract of A. calva flower at different doses- (200 mg/kg, 400 mg/kg and 600 mg/kg of body weight) on Swiss Albino mice models. The sample exhibited moderate central analgesic activity at all doses whereas the acetic acid-induced writhing test in mice revealed 67.69% reduction in peripheral pain response for both 400 and 600 mg/kg doses (69.23% for standard diclofenac sodium). Reduction in diarrheal faeces was found to be 41.03% and 46.46% at dose of 200 mg/kg and 400 mg/kg respectively compared to the standard loperamide 53.85%. Hypoglycemic activity in diabetic mice showed statistically significant data depending on increasing doses and thiopental induced sleeping test revealed the sedative activity (P